Relación entre el nivel sociocultural de los padres y el nivel de desarrollo de las habilidades cognitativas de niños/as de 5 años de edad de la I.E del nivel inicial N°314 – Rupacucha, ciudad Rioja - Espinoza Gómez, Roxana (2012)
The present work of investigation is a fruit of the effort motivated for having to investigate on the general aim that we proposed ourselves since it is of: Determines the relation between the sociocultural level of the parents and the cognitive skills of 5 year old children aces of the Educational lnstitution of the Level of lnitial Education N o 314 - Rupacucha, of the district of Rioja, 2011.For which the population was shaped by the pupils of both sexes of five years of age of the section the 11 snapdragons, that is to say 20 males and 1 O women 11 • Likewise there took an equivalent sample of the parents of the above mentioned children who form a part of the study. The investigation for the class of means used to obtain the information, is of type descriptive; with which one tried to characterize the sociocultural level of the parents and the level of development of the cognitive skills. The type of study is of the type correlaciona!. In the checking of the hypothesis, one determined the obtained results product of the application of the statistical formulae of the coefficient of Pearson's correlation, for the check of the hypothesis, a value being obtained calculated of and a value to tabulate of (obtained of the table of significance of the coefficient of Pearson's correlation with 30 degrees of freedom and 5 % of significancia). In these conditions, the alternate hypothesis is accepted by a confidence of 95 %, which indicates that there exists a positive considerable correlation between the variables and that it is explained by 47,58 % of the population, meaning quells cognitive skills of the children and girls relates directly to the sociocultural level of the parents. There was demonstrated that 23 % of the family parents presents a socioculturallow level, 67% 1 happen and 10% a high sociocultural leve!. 38% of the parents afirmaronque the level of studies is Primary lncomplete, 23 % has 20 % Primary Complete, Secondary lncomplete, 13 % Secondary Completes and only 6 % lncomplete University student achieved a Top Level Not. Likewise is observed that 13 children and girls (43 %) presenta regular development of his cognitive skills, whereas 17 (57 %) presents a high level of development of the above mentioned skills.